When Violence Became Beautiful - Angelova-Igova, Boryana (Philosophical journal of conflict and violence, 2018)
In this article, I will look at violence from a different perspective - that is, violence regarded as beautiful. For too long, this perspective has been neglected, considered taboo, and it is precisely due to the controversial character of what the word represents, and to the double standards used when considering it. Namely that, violence can also be a means of expression in art and sports, emphasizing the qualities of the artist or athlete, as well as having an aesthetic and ethical significance. Such violence, of course, needs to be kept within certain limits and subjected to rules. And, as it turns out, sports rules legitimize violence and make it "beautiful".